2008
DOI: 10.1016/j.biopsych.2007.10.022
|View full text |Cite
|
Sign up to set email alerts
|

The Rostral Anterior Cingulate Cortex Modulates the Efficiency of Amygdala-Dependent Fear Learning

Abstract: Background-The rostral anterior cingulated cortex (rACC) and the amygdala consistently emerge from neuroimaging studies as brain regions crucially involved in normal and abnormal fear processing. The aim of this study is to investigate a possible top-down modulation of a specific rACC sub-region on the acquisition of auditory fear conditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 106 publications
4
85
0
Order By: Relevance
“…Similarly, chemical activation of ACC neurons in rodents induces aversion to the place where the activation occurred 43 . Conversely, bilateral (but not unilateral) chemical inactivation of the ACC inhibited the formation of conditioned fear memory induced by footshock 115,119,120 . Bilateral microinjection of NMDA-receptor antagonists into the ACC also reduced or blocked the formation of a fear memory 57 .…”
Section: Box 1 | Pain Fear and The Anterior Cingulate Cortexmentioning
confidence: 96%
“…Similarly, chemical activation of ACC neurons in rodents induces aversion to the place where the activation occurred 43 . Conversely, bilateral (but not unilateral) chemical inactivation of the ACC inhibited the formation of conditioned fear memory induced by footshock 115,119,120 . Bilateral microinjection of NMDA-receptor antagonists into the ACC also reduced or blocked the formation of a fear memory 57 .…”
Section: Box 1 | Pain Fear and The Anterior Cingulate Cortexmentioning
confidence: 96%
“…Thus, the ACC (and the mPFC in general) are key structures in determining how we deal with the world and are central to inhibitory control (Braver, Barch, Gray, Molfese, & Snyder, 2001;Rubia et al, 2001), reward responses and their modulation (Amiez, Joseph, & Procyk, 2005), aVective resilience (Bissiere et al, 2008;Etkin, Egner, Peraza, Kandel, & Hirsch, 2006), and even top-down inXuence on primary sensory processes (Crottaz-Herbette & Menon, 2006;Sarter, Gehring, & Kozak, 2006) and presumably for higher level functions as well (Koski & Paus, 2000). In other words, the ACC and mPFC are central to control mechanisms dealing with internal states.…”
Section: What Does the Acc Do?mentioning
confidence: 98%
“…A role for the ACC in trace conditioning is further supported by work that found pre-training blockade of NR2B containing NMDARs within the ACC disrupted trace fear in mice (Descalzi et al, 2012). Similar to the PL, the rodent ACC also sends excitatory projections to the amygdala and thus may alter fear expression directly (Bissière et al, 2008). In support, mice with pre-training ACC inactivation showed initial deficits in fear acquisition in a delay fear paradigm (Bissière et al, 2008), conversely humans showed increased ACC activation during both delay and trace fear conditioning (Knight et al, 2004; Milad et al, 2007).…”
Section: Working Memory and Trace Conditioningmentioning
confidence: 99%